Introduction to the physical metallurgy of welding - Easterling, K. E. (Butterworths monographs in materials., 1992)
Introduction to the Physical Metallurgy of Welding deals primarily with the welding of steels, which reflects the larger volume of literature on this material; however, many of the principles discussed can also be applied to other alloys. The book is divided into four chapters, in which the middle two deal with the microstructure and properties of the welded joint, such as the weld metal and the heat-affected zone. The first chapter is designed to provide a wider introduction to the many process variables of fusion welding, particularly those that may influence microstructure and properties, w.